Observed Comfort in Sexual Communication between Mothers and Adolescents. Issue 1 (2nd January 2021) - Malcom, Kathryn E.; Ronis, Scott T.
Abstract: Research on parent-adolescent sexual communication has often used self-report measures despite discrepancies among family members. The current study was designed to use a multi-method approach to better understand mother-adolescent sexual communication. This study examined maternal and adolescent self-reports on sexual communication and observed ratings of mothers' and adolescents' comfort during an interaction task. Participants were recruited from a mid-sized Canadian city and included 68 dyads of mothers and adolescents who were between 12 and 17 years old. Based on an actor-partner interdependence model (APIM), results indicated that mothers' observed comfort was positively associated with adolescent girls' but not boys' reports of sexual communication. Findings suggest the importance of using a multi-method approach to studying parent-adolescent sexual communication and the role of gender in parent-adolescent sexual communication.